Hyaluronic acid therapy in hip osteoarthritis: differential efficacy in secondary osteoarthritis due to inflammatory rheumatic diseases vs. primary osteoarthritis—a step toward phenotyping osteoarthritis - De Lucia, Orazio; Artusi, Carolina; Cumbo, Enrico; Trignani, Giorgia; Sette, Manuel; Ferrito, Matteo; Perino, Miriam; Ingrao, Luca; Amati, Andrea; Murgo, Antonella; Caporali, Roberto (Frontiers in Musculoskeletal Disorders, 2025)
ObjectiveThe hip joint is frequently affected by osteoarthritis (OA) and is a leading cause of disability. This study aims to assess the long-term efficacy of ultrasound-guided intra-articular viscosupplementation for pain relief in patients with hip osteoarthritis secondary to rheumatic diseases compared to primary OA.MethodsThis single-center, retrospective, observational cohort study included patients with hip OA who received intra-articular injections of hyaluronic acid (HA) (Hylan G-F 20). Fisher's exact test was applied to evaluate baseline variables, with 95% confidence intervals (CI) calculated for differences in mean outcomes.ResultsA total of 55 patients with primary hip OA (POA) and 16 patients with secondary hip OA (SOA) were included. The mean observation period was 31.3 months (±29.9), with an average of 5 intra-articular injections administered. Both groups showed a positive response to HA injections, with the POA group demonstrating a mean Visual Analog Scale (VAS) pain reduction of 2.97 (95% CI 2.38–3.56), compared to 1.28 (95% CI 0.18–2.37) in the SOA group. At the end of follow-up, pain reduction was less pronounced in the SOA group, which showed higher residual VAS pain scores compared to the POA group (p = 0.029).ConclusionsThis study highlights that HA injections significantly reduce pain in both primary and secondary hip osteoarthritis. However, patients with primary OA experienced greater pain relief, as evidenced by a more substantial reduction in VAS scores compared to those with secondary OA.